2019
DOI: 10.3390/jof5010004
|View full text |Cite
|
Sign up to set email alerts
|

A Moldy Application of MALDI: MALDI-ToF Mass Spectrometry for Fungal Identification

Abstract: As a result of its being inexpensive, easy to perform, fast and accurate, matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-ToF MS) is quickly becoming the standard means of bacterial identification from cultures in clinical microbiology laboratories. Its adoption for routine identification of yeasts and even dimorphic and filamentous fungi in cultures, while slower, is now being realized, with many of the same benefits as have been recognized on the bacterial side. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 76 publications
1
75
0
4
Order By: Relevance
“…The rate of correct identification obtained for Aspergillus with IDFP medium can be considered as good regarding rates already described in the literature that are very variable ranging from 0% to 100%. 16,19,22,[24][25][26] For non-Aspergillus species, a rate of 73% of correct identification was obtained after 24 hours following complete formic acid acetonitrile extraction. So also in this case, protein extraction is encouraged to obtain optimal results.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of correct identification obtained for Aspergillus with IDFP medium can be considered as good regarding rates already described in the literature that are very variable ranging from 0% to 100%. 16,19,22,[24][25][26] For non-Aspergillus species, a rate of 73% of correct identification was obtained after 24 hours following complete formic acid acetonitrile extraction. So also in this case, protein extraction is encouraged to obtain optimal results.…”
Section: Discussionmentioning
confidence: 99%
“…In diagnostic facilities, matrix-assisted laser desorption ionization-time-of-flight mass spectrometry (MALDI-TOF MS) is being increasingly used for the identification of filamentous fungi. In the last few years, several studies have shown the potential of this method for a fast identification of the Mucorales [108][109][110]. Using the VITEK®MS v3.0 system, a species identification rate of 86% was achieved for 118 mucoralean isolates [111].…”
Section: Identification and Detectionmentioning
confidence: 99%
“…11,12 MALDI-TOF MS is used in the analysis of portions of mycelium and/or conidia from fungal cultures, and is considered to be an accurate and rapid identification method. 13,14 The aim of the present study was to evaluate the application of MALDI-TOF-MS for the identification of and discrimination between A flavus and A oryzae in clinical and environmental samples and compare its diagnostic power with that of β-tubulin gene sequencing. Accumulating evidence suggests that MALDI-TOF MS is a promising approach to rapid and accurate identification of different clinically relevant pathogens, 10,23,24 which was also successfully applied to discriminate among Aspergillus species.…”
Section: Dna Relatedness Among a Flavus A Oryzae A Parasiticus And mentioning
confidence: 99%
“…MALDI‐TOF MS is used in the analysis of portions of mycelium and/or conidia from fungal cultures, and is considered to be an accurate and rapid identification method . The aim of the present study was to evaluate the application of MALDI‐TOF‐MS for the identification of and discrimination between A flavus and A oryzae in clinical and environmental samples and compare its diagnostic power with that of β‐tubulin gene sequencing.…”
Section: Introductionmentioning
confidence: 99%